The Role of GnIH in Biological Rhythms and Social Behaviors - Teo, Chuin Hau; Phon, Brandon; Parhar, Ishwar (Frontiers in Endocrinology, 2021)
Gonadotropin-inhibitory hormone (GnIH) was first discovered in the Japanese quail, and peptides with a C-terminal LPXRFamide sequence, the signature protein structure defining GnIH orthologues, are well conserved across vertebrate species, including fish, reptiles, amphibians, avians and mammals. In the mammalian brain, three RFamide-related proteins (RFRP-1. RFRP-2, RFRP-3 = GnIH) have been identified as orthologues to the avian GnIH. GnIH is found primarily in the hypothalamus of all vertebrate species, while its receptors are distributed throughout the brain including the hypothalamus and the pituitary. The primary role of GnIH as an inhibitor of gonadotropin-releasing hormone (GnRH) and pituitary gonadotrophin release is well-conserved in mammalian and non-mammalian species. Circadian rhythmicity of GnIH, regulated by light and seasons, can influence reproductive activity, mating behaviour, aggressive behaviour and feeding behaviour. There is a potential link between circadian rhythms of GnIH, anxiety-like behaviour, sleep, stress and infertility. Therefore, in this review we highlight the functions of GnIH in biological rhythms, social behaviours, reproductive and non-reproductive activities across a variety of mammalian and non-mammalian vertebrate species.